Initial exploration of a brain age score based on validated computerized cognitive assessments in Japanese individuals: Neuropsychology/Multicultural issues in assessment of dementia. (7th December 2020) - Edgar, Chris J.; Schembri, Adrian; Maruff, Paul T.; Gee, Michelle; Iwatsubo, Takeshi; Aisen, Paul S.; Sperling, Reisa A.; Irizarry, Michael C.
Abstract: Background: Differences between chronological age and biological age can be used to communicate health related information to the general population. For the brain, cognitive performance can be used to define biological age. We utilized data from performance on tests from the Cogstate Brief Battery (CBB) to develop a 'Brain Age' score for characterizing the presence of any cognitive impairment in Japanese older adults at risk of dementia. Methods: To compute an Brain Age, data from the One Card Learning and One Back tests from the CBB was compared to age stratified normative data. Brain Age was computed as the difference in standardized score from age matched normative data. For every point better or worse than the normative mean (0), 0.5 years was added or subtracted from chronological age, to a maximum of 10 years (20 points, or 2 SD). For the current analysis, Brain Age scores were derived for 106 Japanese cognitively normal (CN) individuals from clinical trial screening data for the A4 study and 611 Japanese adults classified with a memory impairment during their screening for the elenbecestat MissionAD program (memory impaired). Differences between these groups were used to determine known groups validity. Results: Mean chronological age was equivalent in the CN (mean = 71.7, SD = 4.6) and memory impaired (mean =72.6, SD= 7.4) samples. Brain Age score was equivalent to chronological age in the CN sample (mean Brain Age = 72.4, SD = 7.45). However in the memory impaired group Brain Age was 6.3 years greater than chronological age (mean Brain Age = 78.9, SD = 8.2). Accordingly, Brain Age was significantly greater in the memory impaired than cognitively normal groups (p < 0.01; d = 0.81). Conclusion: Brain Age score is a valid construct for defining biological age impairment in Japanese individuals at risk for dementia. The current data suggest the presence of a difference between chronological and biological age of approximately six years is a criterion that would warrant more detailed investigations. The Brain Age score may be a useful means for communicating brain health information, including the need to adopt a healthier lifestyle.